Analysis and experimental evaluation of novel hybrid fuzzy‐based sliding mode control strategy for performance enhancement of PV fed DSTATCOM. (2nd February 2021) - Mishra, Soumya; Dash, Santanu Kumar; Ray, Pravat Kumar; Puhan, Pratap Sekhar
Abstract: This article shows the motivation towards the development of a novel hybrid fuzzy‐based sliding mode control scheme for photovoltaic tied DSTATCOM topology for eliminations of perturbations in source currents and reactive power compensation. A LCLC type passive filter is employed at the output of PV fed DSTATCOM, which helps to connect the solar system to a grid. The presence of the series capacitor in the passive filters decreases dc link voltage, which helps in reducing the ratings of DSTATCOM in the proposed system. The switching signals for the PV fed DSTATCOM is generated by the utilization of novel hybrid fuzzy‐based sliding mode control scheme. To improve the efficiency of dc link voltage controller and to regulate the dc link voltage, fuzzy logic‐based approach has been utilized. The controller performance has been compared with conventional algorithms of reference signal generation to analyze the efficiency. An experimental prototype has been developed in the laboratory and results are analyzed to validate the efficiency of the proposed controller. Abstract : This research article presents an advanced hybrid controller for a photovoltaic fed grid connected system to enhance the performance and efficiency for the elimination of power quality issues. A novel hybrid fuzzy‐based sliding mode control scheme has been developed and implemented for the proposed PV fed DSTATCOM system with LCLC passive filter. The efficiency of the proposed controller has been verified through simulation and experimental results. The figure shows the developed experimental structure of the proposed system.